Stated Preferences for Attributes of a CYP2C19 Pharmacogenetic Test Among the General Population Presented with a Hypothetical Acute Coronary Syndrome Scenario - Bereza BG; Coyle D; So DY; Kadziola Z; Wells G; Grootendorst P; Papadimitropoulos EA (Dove Medical Press, 2020)
Basil G Bereza, 1 Doug Coyle, 2 Derek Y So, 3 Zbigniew Kadziola, 4 George Wells, 2 Paul Grootendorst, 1 Emmanuel A Papadimitropoulos 1, 4 1University of Toronto Leslie Dan Faculty of Pharmacy, Toronto, ON, Canada; 2University of Ottawa School of Epidemiology and Public Health, Toronto, ON, Canada; 3University of Ottawa Heart Institute, Ottawa, ON, Canada; 4Eli Lilly & Company, Toronto, ON, CanadaCorrespondence: Basil G BerezaLeslie Dan Faculty of Pharmacy, 144 College Street, Toronto, ON M5S 3M2, CanadaTel +1 416-978-6989Email bgbereza@gmail.comBackground: Pharmacogenetic (PGx) testing identifies pharmacotherapeutic risks to permit personalized therapy. Identifying the genetic profile of patients with acute coronary syndrome (ACS) who are considered for therapy with clopidogrel (P2Y 12 receptor blockers) and acetylsalicylic acid (ASA) contributes to the treatment paradigm. Patient preferences would inform a collaborative framework and by extension inform healthcare policy formulation.Purpose: To quantify stated preferences (willingness to pay) for attributes of a novel point-of-care PGx (CYP2C19) test using a discrete choice experiment (DCE) from the general public in Ontario, Canada, and to identify starting point bias of the cost attribute.Methods: A web survey was created and included a questionnaire, decision board, and a DCE. DCE choice sets include the following attributes (levels): sample collection (blood, finger prick, and cheek swab), turnaround time for results (1 hr, 3 days, and 1 week), and cost in additional insurance premiums. The presence of starting point bias (cost attribute levels of $0, $1, $5 or $0, $2, $10) in the estimation of willingness to pay (WTP) was tested.Results: Estimates for turnaround time and cost attributes were statistically significant. Coefficients related to the starting point bias were also significant. Approximately 67% of survey participants chose the PGx test compared to status quo treatment options. WTP for a 1 hr turnaround time compared to a 1-week turnaround time was $10.77 (95% CI 9.58 -12.25).Conclusion: This translational study shows preference for a point of care PGx test.Keywords: discrete choice experiment, pharmacogenetic test, patient preference, startingpoint bias